Development of an Observation Tool Designed to Increase Cultural Relationships and Responsive Pedagogy to Raise the Achievement of Māori Students in Secondary Classrooms in Aotearoa New Zealand (Journal of Education and Development, 2018)
The paper discusses the development and conventions for use of a classroom observation tool designed to support secondary school teachers in Aotearoa New Zealand to develop respectful learning relationships and culturally responsive pedagogy in their classrooms. This tool was created within a programme of teacher professional development to support the improvement of indigenous Māori students’ achievement and engagement in learning. The Ministry of Education recognised the need for an extensive change in practices across the entire education sector that required a shift in thinking and behaviour. The observation tool was therefore designed to support formative assessment, focused on change, through deliberate and democratic professionalism. Initial data, whilst not conclusive, suggest this tool has the potential to support more effective cultural relationships and responsive pedagogy in classrooms thus improving learning and engagement among Māori students through increased self-efficacy, pride and a sense of themselves as culturally located.